The Threshold Effect: Lipopolysaccharide-Induced Inflammatory Responses in Primary Macrophages Are Differentially Regulated in an iRhom2-Dependent Manner - Skurski, Joseph; Dixit, Garima; Blobel, Carl P.; Issuree, Priya D.; Maretzky, Thorsten (Frontiers in Cellular and Infection Microbiology, 2021)
A well-controlled innate immune response is characterized by a rapid yet self-limiting inflammatory response. Although much is known about the range of inflammatory stimuli capable of triggering an innate immune response, the mechanisms which govern the degree of inflammation induced by inflammatory insults and the mechanisms in place to reset or maintain homeostasis are poorly understood. Tumor necrosis factor (TNF) is a potent early response pro-inflammatory cytokine produced by immune cells following a broad range of insults spanning autoimmunity and metabolic diseases to pathogenic infections. Previous studies have shown that a disintegrin and metalloproteinase (ADAM) 17 controls the release of soluble TNF and epidermal growth factor receptor signaling. Utilizing a genetic model of ADAM17 deficiency through the deletion of its regulator, the inactive rhomboid 2 (iRhom2), we show that loss of ADAM17 activity in innate immune cells leads to decreased expression of various cytokines in response to low levels of pathogen-associated molecular pattern (PAMP) stimulation but not at high dose stimulation. In addition, TNF receptor (TNFR) 1/2-deficient bone marrow-derived macrophages yielded significantly reduced TNF expression following low levels of PAMP stimulation, suggesting that signaling through the TNFRs in immune cells drives a feed-forward regulatory mechanism wherein low levels of TNF allow sustained enhancement of TNF expression in an iRhom2/metalloproteinase-dependent manner. Thus, we demonstrate that inflammatory expression of TNF and IL1B is differentially regulated following high or low doses of PAMP stimulation, invoking the activation of a previously unknown regulatory mechanism of inflammation.